2017
DOI: 10.5588/pha.16.0123
|View full text |Cite
|
Sign up to set email alerts
|

Childhood tuberculosis in Mauritania, 2010–2015: diagnosis and outcomes in Nouakchott and the rest of the country

Abstract: The National Tuberculosis Programme, Mauritania. To compare the diagnosis and treatment outcomes of childhood tuberculosis (TB) cases (aged<15 years) registered between 2010 and 2015 inside and outside Nouakchott, the capital city. This was a retrospective comparative cohort study. A total of 948 children with TB were registered. The registration rate was 10 times higher in Nouakchott. The proportion of children among all TB cases was higher inside than outside Nouakchott (7.5% vs. 4.6%, < 0.01). Under-fives r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
6
2
Order By: Relevance
“…Half of those unsuccessful outcomes were loss to follow-up and less than a quarter were deaths. These percentages are considerably lower than the majority of reports in the literature which, since 2016, range from 4.1% in The Netherlands [ 15 ] to 39.0% in Mauritania [ 12 ]. Two other recent reports of DS-TB treatment outcomes of children in Pakistan found that 4.9% [ 21 ] and 14.6% [ 9 ] experienced unsuccessful outcomes.…”
Section: Discussionmentioning
confidence: 64%
“…Half of those unsuccessful outcomes were loss to follow-up and less than a quarter were deaths. These percentages are considerably lower than the majority of reports in the literature which, since 2016, range from 4.1% in The Netherlands [ 15 ] to 39.0% in Mauritania [ 12 ]. Two other recent reports of DS-TB treatment outcomes of children in Pakistan found that 4.9% [ 21 ] and 14.6% [ 9 ] experienced unsuccessful outcomes.…”
Section: Discussionmentioning
confidence: 64%
“…Moreover, hospital-based studies often showed a higher rate of severe TB disease [ 33 ] and thus a lower proportion of treatment success. Two kinds of databases are useful to monitor the outcomes of TB, whether success or unsuccessful treatment [ 9 , 33 , 34 ]. The MyTB version 2.1 database includes a large number of variables, such as place of treatment, BCG scars, treatment regime, directly observed therapy (DOT) for the intensive phase, and DOT supervisor.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that young children less than five years of age had an increased risk of unsuccessful treatment outcomes compared to older children, which is consistent with findings from other studies. [7,9,18] TB diagnosis in young children is often delayed due to the presentation of non-specific symptoms, a need to rule out other pathogens[4], and the inability of young children to produce a sputum specimen to confirm the presence of TB disease. [5] Waiting for a clinical diagnosis may have delayed treatment initiation and, ultimately, led to disease progression to a more severe state.…”
Section: Discussionmentioning
confidence: 99%
“…Among children who are diagnosed with TB disease and initiate treatment, some groups may be at higher risk of experiencing unsuccessful treatment outcomes, including death or being lost to follow-up. Previously identified risk factors for unsuccessful treatment outcomes in children with TB include being HIV positive[7,8], being less than five years of age[7,9], having low body weight[10], and smear positivity. [11] The role of these and other risk factors may vary by setting and population.…”
Section: Introductionmentioning
confidence: 99%